Ergonomics Intervention to Improve Occupational Health of Workers in Malaysian Metal Stamping Industry - Isa , Halim (2007)
In a new era of industrialized world, occupational health plays an important role in maintaining and maximizing competitiveness as well as productivity in Malaysian Metal Stamping Industry. Occupational health is considered as lifeblood and believed to be one of the vital contributor to the success of such industry. Hence, the issues on occupational health services in metal stamping need to be addressed to ensure the competitiveness of the industry in global future market. The objectives of the research are to assess current working posture, muscles activity and energy consumption and propose a solution that would improve the occupational health of workers in Malaysian Metal Stamping Industry. Two male workers performing manual metal stamping process participated in this research. Ergonomics assessment tools such as REBA Software, surface Electromyography (sEMG) and oxygen analyzer were used simultaneously to assess and interpret the data of working posture, muscles activity and energy consumption of workers respectively. Based on the results obtained, improper workstation design was identified as the main contributor to poor occupational health. The design of the workstation has been improved using ergonomic intervention to improve occupational health. The intervention was found to be an effective solution and positively improve occupational health in metal stamping industry.